Measurement of Tourist Experience Satisfaction of Sports Tourism Based on Psychological Capacity Analysis - Hong Huo; Dongdong Zhang; Haibin Wang, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2022)
Psychological capacity testing can successfully reconcile the conflict between the growth of sports tourism and the desire for visitor satisfaction. Existing research on psychological capacity analysis has not provided a comprehensive theoretical framework or considered the relationship between psychological capacity analysis and tourist satisfaction evaluation. This research conducts a psychological capacity analysis of tourist experience satisfaction in sports tourism to address these issues. To begin, a psychological capacity analysis was driven from the standpoint of sports tourism tourist experience, the processes of fuzzy comprehensive evaluation (FCE) were provided, and suitable psychological capacity measuring indices were chosen to create an evaluation index system (EIS). Following that, a grey relational analysis (GRA) was used to quantify and evaluate the tourist experience satisfaction associated with sports tourism, followed by a gap analysis of the tourist experience satisfaction associated with sports tourism. The psychological capacity of tourists was explored by age group and gender in experiments and the relationship between tourist experience satisfaction and tourist volume. The experimental results illustrate the efficacy of our technique for analyzing psychological capability and quantifying satisfaction. We achieved the pertinent measured data on tourist satisfaction with sports tourism.